Running with the Kenyans : passion, adventure, and the secrets of the fastest people on earth - Finn, Adharanand (New York : Ballantine Books, 2012)
Whether running is a recreation, a passion, or just a spectator sport, Finn's incredible journey to the elite training camps of Kenya will captivate. Part travelogue, part memoir, this quest uncovers the secrets of the world's greatest runners--and puts them to the test.
Keywords: Runners (Sports) -- Kenya; Running -- Social aspects -- Kenya; Track and field -- Social aspects -- Kenya; National characteristics, Kenyan